DESCRIPTION OF VEGETABLE AND FRUIT CONSUMPTION PATTERNS AND LEVELS OF BLOOD GLUCOSE OF DIABETES MELLITUS PATIENTS IN WANGAYA DENPASAR REGIONAL GENERAL HOSPITAL - Komang Novia Frilly Permata Sari; Lely Cintari; Gusti Ayu Dewi Kusumayanti (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2020)
Diabetes mellitus is a group of metabolic diseases with characteristics of hyperglycemia that occur due to abnormal insulin secretion, insulin performance or both. Diabetes Mellitus has increased every year. The pattern of consumption of vegetables and fruits is very closely related to blood glucose levels of people with Diabetes Mellitus. This study aims to describe the consumption patterns of vegetables and fruits and blood glucose levels of people with Diabetes Mellitus at the Wangaya Regional General Hospital, Denpasar. This type of research is observational research with cross-sectional design and collaborative techniques. The number of samples studied were 33 samples. From the research that has been done, the sample with less vegetable consumption and normal blood glucose level is 60.61%, the sample with the type of vegetable consumption does not vary by 48.48%, the sample with the frequency of consumption of rare vegetables and normal blood glucose levels is 54, 55%. Samples with less fruit consumption and normal blood glucose levels were 57.58%, samples with different types of fruit consumption and normal blood glucose levels were 60.61%, and samples with frequency of consumption of rare fruits and normal blood glucose levels were 60, 61%. Keywords: Blood glucose levels; pattern of consumption; diabetes mellitus